The association between training load and injury risk in elite youth soccer players: a systematic review and best evidence synthesis - Verstappen, S.; van Rijn, R. M.; Cost, R.; Stubbe, J. H. (Sports Medicine - Open, 2021)
Background: Injury risk in elite youth soccer players is high. Implementing an optimal training load is of utmost importance to reduce the risk of injuries. Objective: To conduct a systematic review and best evidence synthesis to explore the effects of internal and external training load on injury risk in elite youth soccer players. Methods: MEDLINE, Embase, Web of Science, CENTRAL, and CINAHL were searched up until 17 January 2020. Each article had to meet all of the following criteria: (1) the study population consisted of male elite youth soccer players aged between 12 and 21 years; (2) a longitudinal, prospective study design was used; (3) soccer-related injuries were registered (i.e., self-reported or by medical staff); (4) external and/or internal load parameters were described; and (5) the article was published in an English peer-reviewed scientific journal. The quality of the included articles was assessed using the Newcastle-Ottawa Quality Assessment Scale (NOS). A best evidence synthesis was performed to rank the level of evidence. Results: Five studies (2 high quality, 3 low quality) were included. Best evidence synthesis highlighted that there was moderate evidence for (1) no association between 2-, 3-, and 4-week cumulative loads for total distance covered; (2) no association between 1-week workloads (sRPE × duration); and (3) no association between A:C workload ratios (4 weeks) and injury risk. For all other comparisons, only insufficient or conflicting evidence was found. Conclusion: There is a paucity of evidence for an association between internal and external training load parameters and injury risk in elite youth soccer players.